Leveraging meatpacking ownership concentration and community centrality to improve disease resiliency - Saitone, Tina L.; Schaefer, K. Aleks; Scheitrum, Daniel P. (Frontiers in Sustainable Food Systems, 2022)
The U.S. meat processing sector has been subject to amplified scrutiny after workers exhibited disproportionately high rates of COVID-19 infections and deaths. In response, Tyson Foods—one of the largest meat packers in the country—mandated that its employees be vaccinated against COVID-19 by November 1, 2021. In this paper, we investigate the impact that the Tyson vaccine mandate had on vaccine uptake, infection rates, and deaths in counties where Tyson processing facilities are located. We find that the mandate resulted in approximately 35,000 additional vaccinations. The resultant vaccine uptake avoided 98 COVID-19 infections per day and nearly 75 COVID-19-related deaths; the associated public health savings total 45.4 million. Employee health-related interventions at the corporate level can leverage industry ownership concentration and the centrality of packing operations in host communities to improve health outcomes and disease resiliency well beyond the packing operations.